2015
DOI: 10.1021/acs.joc.5b01248
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Thioetherification Reactions of Alkyl Halides, Triphenyltin Chloride, and Arylboronic Acids with Nitroarenes in the Presence of Sulfur Sources

Abstract: In this article, we report three odorless methods for the thioarylation and thioalkylation of different nitroarenes using alkyl halides (Br, Cl), triphenyltin chloride, and arylboronic acids as the coupling partners. Triphenyltin chloride is capable of delivering all of its phenyl groups to the product. Depending on the reaction, sodium thiosulfate pentahydrate (Na2S2O3·5H2O), S8/KF, and S8/NaOH systems are found to be effective sources of sulfur in the presence of copper salts. The use of green solvents, inex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 85 publications
0
51
0
Order By: Relevance
“…The nitro group of nitroaryl compounds 539 could act as a leaving group and was employed in the thioarylation using triphenyltin chloride 540 (Scheme ) . This stannane is capable of delivering all of its phenyl groups to the product (0.35 equiv.…”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitro group of nitroaryl compounds 539 could act as a leaving group and was employed in the thioarylation using triphenyltin chloride 540 (Scheme ) . This stannane is capable of delivering all of its phenyl groups to the product (0.35 equiv.…”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%
“…Arylboronic acids could also be used as coupling partners with nitroarenes 539 under similar conditions (Scheme ) …”
Section: Sulfur As Building Block – Sulfuration Reactionsmentioning
confidence: 99%
“…In an independent work, we have reported copper-catalyzed denitrative thioetherification using nitroarenes as the coupling partner. 68 The reaction of nitroarenes with triphenyltin chloride and S 8 gave the desired product in excellent yields (Scheme 58). Under the optimized conditions, KF was used as the activator of S 8 , and K 2 CO 3 as the most suitable base.…”
Section: Reactions Involving C-n Bond Cleavagementioning
confidence: 99%
“…We have recently employed sodium thiosulfate as the sulfur source for the synthesis of sulfides from alkyl halides and nitroarenes (Scheme 70) 68. Optimization studies showed a mixture of PEG and H 2 O to be the most effective medium for this reaction.…”
mentioning
confidence: 99%
“…Suzuki cross‐coupling reactions with heterogeneous nano‐palladium catalysts have been studied by several researchers . Triphenyltin chloride (TPTCl) is a very good reagent in organic synthesis such as thioetherification and C&bond;C coupling reactions . Although TPTCl has been applied as a useful reagent for the synthesis of sulfides through C&bond;S coupling reactions, it was shown to be toxic to the rotifer Brachionus koreanus across different levels of biological organization, and should be handled with care.…”
Section: Introductionmentioning
confidence: 99%